ANALISIS PENGARUH HARGA MINYAK DUNIA, INFLASI, DAN SUKU BUNGA TERHADAP RETURN SAHAM PERUSAHAAN IDXENERGY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mohamed Khalipatullah (2022)
This research aims to analyze the effect of world oil prices, inflation, and interest rates on stock returns of IDXENERGY companies listed on the Indonesia Stock Exchange. Purposive sampling method is used for this research, and a total sample of 34 companies was obtained based on predetermined criteria. Panel data regression analysis in this study was conducted using EViews program version 12 with a significance level of 5%. Based on the results of hypothesis testing for each variable, it is concluded that (1) world oil prices have a negative effect on stock returns; (2) inflation has no effect on stock returns; (3) interest rates have a negative effect on stock returns.